2022
DOI: 10.3390/ijms23115991
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of A Combined Treatment of Glioblastoma U251 Cells with An Anti-miR-10b-5p Molecule and An AntiCancer Agent Based on 1-(3′,4′,5′-Trimethoxyphenyl)-2-Aryl-1H-Imidazole Scaffold

Abstract: (1) Background: In the development of new and more effective anticancer approaches, combined treatments appear of great interest. Combination therapy could be of importance in the management of glioblastoma (GBM), a lethal malignancy that accounts for 42% of cancer of the central nervous system, with a median survival of 15 months. This study aimed to verify the activity on a glioblastoma cancer cell line of one of the most active compounds of a novel series of tubulin polymerization inhibitors based on the 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In Singh et al, miR-155 mitigates angiotensin II receptor type-1-mediated angiogenesis to suppress GBM growth [ 81 ]. Zurlo et al suggested the combined use of an anti-miR-10b-5p and a 1-(3′,4′,5′-trimethoxyphenyl)-2-aryl-1 H -imidazole derivative as potential strategy against GBM to improve the efficacy of antitumor therapy and reduce side effects at the same time [ 82 ]. He et al concluded that miR-210-3p can inhibit glioma growth, migration, and proliferation by targeting the iron–sulfur cluster assembly protein (Iscu) gene in mouse models [ 83 ].…”
Section: Microrna-based Therapeutics Against Glioblastomamentioning
confidence: 99%
“…In Singh et al, miR-155 mitigates angiotensin II receptor type-1-mediated angiogenesis to suppress GBM growth [ 81 ]. Zurlo et al suggested the combined use of an anti-miR-10b-5p and a 1-(3′,4′,5′-trimethoxyphenyl)-2-aryl-1 H -imidazole derivative as potential strategy against GBM to improve the efficacy of antitumor therapy and reduce side effects at the same time [ 82 ]. He et al concluded that miR-210-3p can inhibit glioma growth, migration, and proliferation by targeting the iron–sulfur cluster assembly protein (Iscu) gene in mouse models [ 83 ].…”
Section: Microrna-based Therapeutics Against Glioblastomamentioning
confidence: 99%
“…An interesting approach that employs combined treatment has been recently proposed by our group, associating compounds interfering with tubulin polymerization and specific antimiRNA molecules targeting upregulated oncomiRNAs (such as miR-221-3p or miR-10b-5p). Combined treatment appears to have synergistic effects on the activation of apoptosis and cell-cycle alterations, demonstrating that this therapeutical strategy can increase the efficacy of anticancer treatments [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells in the early stage of the apoptotic process (represented in lower right quadrants in the plots) were stained with the Annexin V-PE conjugated; cells in the late phase of apoptosis (upper right quadrants) were stained with Annexin V-PE plus 7-AAD; the necrotic cells were stained only by 7-AAD (upper left quadrants) while live cells showed no staining (lower left quadrants). Following that, samples were obtained using a Guava ® Muse ® Cell Analyzer (Luminex Corporation, Austin, TX, USA), and data was analyzed using the Luminex Annexin V and Dead Cell Software Module (as previously reported [ 8 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…n. MCH100105) at room temperature and protected from light for 20 min. The samples were then analyzed using Guava ® Muse ® Cell Analyzer and data were acquired by utilizing Annexin V and Dead Cell Software Module (Luminex Corp., Austin, TX, USA), as previously reported [ 23 ].…”
Section: Methodsmentioning
confidence: 99%